Mazur spaces. (1981) - Wilansky, Albert
Abstract : A Mazur space is a locally convex topological vector spaceX such that everyf ϵ X s is continuous whereX s is the set of sequentially continuous linear functionals onX ;X s is studied whenX is of the formC ( H ), H a topological space, and whenX is the weak* dual of a locally convex space. This leads to a new classification of compactT 2 spacesH, those for which the weak* dual ofC ( H ) is a Mazur space. An open question about Banach spaces with weak* sequentially compact dual ball is settled: the dual space need not be Mazur.